Evolução das ideias sobre números imaginários - Oliveira, Leandro Sales Almeida de (2015)
In this paper it will be studied the imaginary numbers and how their evolution over time occurred. Such evolution has occurred at a slow pace until it reached at what is known today as the imaginary number i. However, the creation of the complex was not the end of the study of imaginary numbers. These studies have introduced even more comprehensive concepts creating sets as quaternions, extension of four dimensions of the complex. It will be concluded, with the extensions of eight and sixteen dimensions of the complex numbers, known as octonions and sedenions, respectively. Additionally, it will be submitted some applications of these extensions, also known as hypercomplex numbers.